Purification and Characterization of Plantaricin YKX and Assessment of Its Inhibitory Activity Against Alicyclobacillus spp. - Pei, Jinjin; Jin, Wengang; Wang, Jinze; Huang, Yigang; Li, Xinsheng; Zhang, Hongxia; Zhang, Yonggui; Ramadan, Amer; Abd El-Aty, A. M. (Frontiers in Microbiology, 2021)
Consumers prefer natural over synthetic chemical preservatives on a food label. Therefore, it is crucial to ensure the safety and efficacy of such natural preservatives. The emergence of heat-resistant spore-forming Alicyclobacillus spp. has caused spoilage problems in the fruit juice industry. Herein, a bacteriocin-producing stain YKX was isolated from the traditional pickles in Hanzhong City, China, and it was identified as Lactobacillus plantarum by morphological, biochemical, physiological, and genotypic features. A stable bacteriocin, plantaricin YKX, was isolated, purified, and tested for its efficacy against Alicyclobacillus acidoterrestris. Plantaricin YKX is a 14-amino acid peptide (Lys-Tyr-Gly-Asn-Gly-Leu-Ser-Arg-Ile-Phe-Ser-Ala-Leu-Lys). Its minimal inhibitory concentrations (MICs) against the tested bacterial and fungal strains were ranged from 16 to 64 µg/mL. It is thermostable and active at pH 3-8. The flow cytometry data and microscopic observations suggested that plantaricin YKX can augment cell membrane permeability, induce potassium ion leakage and pore formation, and disrupt cell membranes. It also affects spore germination and guaiacol production of A. acidoterrestris, probably due to upregulation of the luxS gene linked to quorum sensing.